The dynamics of utility in the neoclassical OLG model - Wolfgang Kuhle (Max Planck Institute for Research on Collective Goods, 2012)
This paper develops a method to study how life-cycle utility of a sequence of cohorts converges towards its steady state level in the neoclassical two-generations-overlapping model. This method allows to characterize utility changes associated with variations in exogenous policy parameters along the entire transition path between two steady states. At the same time it is not more complicated than a pure steady state analysis. Moreover, it can be applied to economies for which an explicit solution of the transition path is not available.
Keywords: E13; 330; overlapping generations; transition path; utility dynamics